Desenvolvimento local do microterritório de Santos Dumont - MG - Oliveira, Gabriel Marcos Ferreira de (2021)
The main objective of this work is to discuss local development from the perspective of developmental theories, in addition to understanding how, in the contemporary context, the issue of development has been dealt with through the acknowledgment of the importance of public power, citizens, and institutions in the process of regional economic development. Therefore, it is necessary to understand the role of endogenous factors in the territory and their contribution to driving the local economy. This study is split into two sections: The first section aims to contextualize the theories of economic development and the different works regarding local development; furthermore, in the second section, we present a case study on the Microterritory of Development of Santos Dumont - MG, which spans five municipalities: Santos Dumont, Aracitaba, Oliveira Fortes, Ewbank da Câmara and Antônio Carlos. This work makes it possible to glimpse, through the historical formation of the Microterritory, the possible potentialities, and capacities, as well as to identify initiatives that correspond to the local development, understanding the possible solutions to the development and how they are interconnected with the presence of local institutions. The research starts from three theoretical assumptions: the dependence of the micro-region on the regional pole city, Juiz de Fora; the unstructured local development among the municipalities belonging to the study micro-region; and the non-existence of a direct means of popular participation or communication that decentralize political decisions that often are not focused on the most relevant local problems of the population. Through semi-structured interviews with local actors inserted in the most diverse areas related to local development, it was possible to understand how the development process takes place in the Microterritory. Therefore, a survey was carried out regarding the process of local development, in addition to identifying the institutions that, in the view of the interviewees, helped or are still relevant for the territory to be developed. Because of this, it is detected that the Microterritory has local potential and capabilities, especially concerning tourism, agribusiness, education, health, and the goods and services sector, which need investment to shortly, start the local development of the territory in this study.